Electric Potential Value of Microbial Fuel Cell Technology from Chinese Food Restaurant Waste Using Variation of Electrode Pairs - Jaya, Danang; Widawati, Tunjung Wahyu; Ellysa, Firda; Nugroho, Singgih Adi (RSF Conference Series: Engineering and Technology, 2022)
Indonesia’s rapid population growth means that power demand will continue to rise year after year. Indonesia’s growing population has resulted in an increase in restaurants, including Chinese food restaurants. As the number of restaurants grows, so does the amount of waste produced. Microbial Fuel Cells (MFC) that create electrical energy are one solution to this challenge. The study aimed to explore the utilization of MFC systems for power generation. It measured the performance of MFC in liquid waste in generating electrical value by utilizing a series of electrode types, particularly Aluminum (Al), Copper (Cu), Zinc (Zn), and Lead (Pb), and a blend of the four types of electrodes. The measured electrical value indicated that MFC can produced the high electrical voltage value was the pair of zinc (anode) and copper (cathode) of (0.863 V) and then the highest electric current value is 0.14 mA with electrode Cu and Zn. The maximum power density is 0.00464 W/m2 using a combination of Zn/Cu electrodes and then electrical energy with highest value is 0.75168 J with Zn/Cu.